Mexico Under Spanish Rule: Historical Impact Until 1821 - Iman Hamid Kazim; Dr. Abbas Muhammad Jamil (Indonesian Journal of Islamic Studies, 2026)
General Background Colonial administrative frameworks play a decisive role in shaping the long-term socio-political structures and eventual sovereignty movements of occupied territories. Specific Background For nearly three hundred years, Mexico functioned as a central base of the Spanish Empire, governed under a rigid centralized viceroyalty that strictly regulated institutional, economic, and social systems. Knowledge Gap While conventional histories outline the sequential timeline of anti-colonial uprisings, there remains a lack of integrated structural focus on how specific class stratification policies and shifting transatlantic geopolitical shocks combined to transform localized unrest into a successful consensus for independence. Aims This study analyzes the historical trajectory of Spanish colonial administration in Mexico and evaluates the internal systemic factors and revolutionary phases that culminated in independence in 1821. Results The investigation demonstrates that institutionalized social discrimination against the Creole, Mestizo, and native populations, paired with systemic economic monopolies and the geopolitical chaos of the Napoleonic wars, directly accelerated the collapse of colonial authority. Novelty This paper provides a consolidated narrative framework tracking how fragmented social rebellions successfully transitioned into a coordinated political consensus under the Plan of Iguala. Implications The findings offer critical insights for historians studying colonial governance, emphasizing that the long-term sustainability of imperial rule is fundamentally undermined when institutional privileges remain completely detached from domestic social realities. Keywords: Mexico, Colonial Administration, Hernan Cortes, Revolutionary Uprisings, Mexican Independence Key Findings HighlightsThe Spanish colonial apparatus maintained strict political and economic control over Mexico for nearly three centuries through a rigid centralized viceroyalty. Long-term socio-economic discrimination against indigenous populations and Creoles acted as the primary driver for widespread revolutionary sentiment. Transatlantic political disruptions caused by Napoleon's invasions provided the ultimate geopolitical catalyst for the successful implementation of the Plan of Iguala.